Changes in clinical disease activity are weakly linked to changes in MRI inflammation on treat-to-target escalation of therapy in rheumatoid arthritis - Fiona M. McQueen; Peter Chapman; Terina Pollock; Dena D’Souza; Arier C. Lee; Nicola Dalbeth; Lisa Stamp; Karen Lindsay; Anthony Doyle (Arthritis Research & Therapy, 2017)
Abstract Background Rheumatoid arthritis (RA) treat-to-target (T2T) regimens often use the disease activity score (28 joints) incorporating C-reactive protein (DAS28CRP) as an outcome measure. We compared changes in the DAS28CRP with changes in magnetic resonance imaging (MRI) inflammation on treatment escalation. Methods Eighty seropositive RA patients with active disease were enrolled. Group A (N = 57) escalated to another conventional disease-modifying therapy (cDMARD) combination, and Group B (N = 23) to anti-TNF therapy/cDMARDs. Contrast-enhanced 3T-MRI wrist scans were obtained before and 4 months after regimen change. Scan pairs were scored for inflammation (MRI(i)) and damage. Disease activity was assessed using the DAS28CRP. Results Eighty patients were enrolled and 66 MRI scan pairs were available for analysis. Intra-reader reliability was high: intraclass correlation coefficient (average) 0.89 (0.56–0.97). ΔDAS28CRP did not differ between groups: Group A, −0.94 (−3.30, 1.61); Group B, −1.53 (−3.59, 0.56) (p = 0.45). ΔMRI(i) also did not differ: Group A, 0 (−25, 10); Group B, −1 (−15, 28) (p = 0.12). Combining groups, ΔMRI(i) correlated weakly with ΔDAS28CRP (Spearman’s 0.36, p = 0.003). Using multiple linear regression analysis adjusting for confounders, ΔDAS28CRP was associated with ΔMRI(i) (p = 0.056). Of the individual MRI measures, only Δtenosynovitis correlated with ΔDAS28CRP (Spearman’s 0.33, p = 0.007). ΔMRI(i) was negatively associated with the MRI erosion score at entry (p = 0.0052). Conclusions We report the first study investigating the link between changes in clinical and imaging inflammation in a real-world RA cohort escalating to conventional and biologic DMARDs. The association was significant but relatively weak, suggesting that MRI targets cannot yet be advocated as outcomes for T2T escalation. Trial registration ANZCTR 12614000895684 . Registered 22 August 2014.